Simulasi Pengaruh Variasi Konduktor Berkas Terhadap Gangguan Berisik Dan Radio Interferensi Pada Saluran Udara Tegangan Ekstra Tinggi 275kV - Sonong Sonong; Herman Nawir; Fitrawati Suharti; Insan Kamil (Politeknik Negeri Ujung Pandang, 2019)
The use of extra-high voltage lines can increase efficiency and reduce voltage drop but cause corona generation. Corona that occurs increases channeling losses and causes disruption to the environment in the form of Audible Noise (AN) and Radio Interference (RI). Audible Noise (AN) and Radio Interference (RI) that are too large will disturb the community around the transmission line. The use of a bundle conductor is a way to reduce the risk of corona. This paper discusses the effect of variations in the bundle conductor on noise interference and radio interference in 275kV extra-high-voltage air lines (SUTET). The types of variations include variations in the number of beams, variations in the distance between sub-conductors, and variations in diameter of the conductor. Next, the Audible Noise (AN) and Radio interference (RI) values are calculated for the Latuppa (Palopo) - Pomana channel planning. The results of the calculation of AN and RI values on SUTET 275kV are still included as safe criteria because the value is still below the criteria limits of Perry and SPLN 46-1-1981 concerning the Noise Level Limitation Guidelines and the IEEE Radio Noise Design Guide about the maximum limit of RI.